Assessment of factors influencing the citation level of scientific publications in the field of sport and physical activity - Sergii Iermakov; Georgiy Korobeynikov (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. The citation level of scientific publications is a key indicator of their scientific impact and significance. With the increasing number of publications in the field of sport and physical activity, it is crucial to identify the factors influencing citation levels. The aim of this study is to analyze the relationship between the number of cited references and the citation level of publications. Additionally, the study examines the impact of access mode (open or closed) and publication type on citation metrics.